Expanding community engagement in HIV clinical trials: a pilot study using crowdsourcing. (1st July 2020) - Day, Suzanne; Mathews, Allison; Blumberg, Meredith; Vu, Thi; Mason, Hailey; Rennie, Stuart; Kuruc, JoAnne D.; Gay, Cynthia L.; Margolis, David M.; Tucker, Joseph D.
Abstract : Objective: To assess the potential for crowdsourcing to complement and extend community advisory board (CAB) feedback on HIV clinical trials. Crowdsourcing involves community members attempting to solve a problem and then sharing solutions. Methods: CAB and crowdsourced approaches were implemented in the context of a phase 1 HIV antibody trial to collect feedback on informed consent, participation experiences, and fairness. CAB engagement was conducted through group discussions with members of an HIV CAB. Crowdsourcing involved open events intended to engage the local community, including interactive video modules, animated vignettes, and a creative idea contest. Open coding and analysis of emergent themes were conducted to compare CAB and crowdsourced feedback. Results: The crowdsourcing activities engaged 61 people across three events; nine people engaged in CAB feedback. Compared with CAB participants, crowdsourcing participants had lower levels of education and income, and higher levels of disability and unemployment. Overlap in CAB and crowdsourced feedback included recommendations for enhancing communication and additional support for trial participants. Crowdsourcing provided more detailed feedback on the impact of positive experiences and socio-economic factors on trial participation. CAB feedback included greater emphasis on institutional regulations and tailoring trial procedures. Crowdsourced feedback emphasized alternative methods for learning about trials and concerns with potential risks of trial participation. Conclusion: Conducting crowdsourcing in addition to CAB engagement can yield a broader range of stakeholder feedback to inform the design and conduct of HIV clinical trials. Video abstract: http://links.lww.com/QAD/B707 Abstract : Supplemental Digital Content is available in the text